Loss minimization of optimal power flow with stochastic solar power generation using improved salp swarm algorithm - Zuriani, Mustaffa; Mohd Herwan, Sulaiman (Springer Science and Business Media Deutschland GmbH, 2022)
This paper proposes an improvement of bio inspired metaheuristic algorithm namely Salp Swarm Algorithm (ISSA) which later to be implemented in solving the Optimal Power Flow (OPF) problem. OPF is a well-known optimization problem in power system operation and the proposed ISSA has been utilized to solve one of the objective functions viz. loss minimization. The presence of stochastic solar power generation also has been considered in this paper. To show the potential of the proposed ISSA, the technique is tested on modified IEEE 30-bus system. The performance of ISSA is compared with original SSA and another metaheuristic algorithm. From the simulations that have been conducted, it can be concluded that the ISSA is better compared to others in terms of loss minimization solution, which is more than 50% loss reduction compared to the original SSA.